Integrasi Al-Qur'an dan Ilmu Sosial (Kontekstualitas al-Qur'an dalam Kehidupan Bermasyarakat) - Ahmad, Hasbullah (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2021)
The dialectic between the text and reality has occurred since the beginning when the Qur'an was revealed. The evidence caused the emergence of the term asba>b al-nuzu>l in some verses of al-Qur'an. However, al-Qur’an is the true Book, even in the past, present or for the future. Related to the future, al-Qur'an is always relevant as time and place change. However, it was not realized properly so that the dialectic seems to have stopped at the time the Qur'an was revealed. The Qur'an no longer goes hand in hand with the ever-changing social reality. From this phenomenon, there is an impression as if al-Qur'an is always a few steps behind when social phenomena are always present with new nuances and colors. Therefore, it should need an effort to keep the dialectic of al-Qur'an in accordance with the existing reality. This study would like to suggest that among the steps to maintain the above dialectic is to integrate the knowledge of al-Qur'an with social sciences such as; sociology, anthropology and history. Al-Qur'an neesds to be understood and interpreted by looking at the socio-cultural and historical conditions when it was revealed. This is where contemporary hermenetic theory can be used by examining the relationship between the text, the commentator and the society to which the verses of the Qur'an were revealed. Then from the picture of the past, the contextualization of the verses of the Qur'an can be narrated to the current condition of society.